Ultrasonological evaluation of acute scrotum - Sharma, Prakash; Gyawali, Merina; Singh, Sristi (Nepalese Journal of Radiology, 2018)
Introduction: Acute scrotum is a common surgical condition. Ultrasound along with Doppler plays an important role in differentiating the various causes. Purpose of this study was to evaluate the role of ultrasound in identifying the various causes of acute scrotum. Methods: All patients with history of acute scrotum presenting to the Department of Radiology were included in the study. Scrotal ultrasound was performed with a linear 7.5 to 12-MHz transducer with abundant acoustic gel. Imaging was done in longitudinal and transverse planes with Power Doppler and Color Doppler. The testes, epididymis, spermatic cord, scrotal wall and inguinal region were evaluated. Kidney, Ureter and Bladder region was evaluated for possibility of calculus. Final diagnosis was made based on clinical outcome, follow up, intraoperative findings and histopathology when available. Statistical analysis was done using SPSS version 18 for windows. Descriptive analysis was done. Non parametric correlation between side and torsion was done using Kendall Rank Correlation Coefficient. Results: There were altogether 50 patients available for statistical analysis. Age of the patients ranged from 14 to 65 years with mean age of 34.7±14.7 years. Most common age group was 21 to 40 years. Inflammatory pathology was the most common pathology of actual scrotal pain. There was no significant correlation between side of pain and testicular torsion. Conclusion: Inflammatory pathology was the most common cause for actual scrotal pain. The most common age group was 21 to 40 years.